Evaluation of Metal‐Organic Framework MIL-89 nanoparticles toxicity on embryonic zebrafish development - Dana E. Al-Ansari (16327350) (2022)
Metal-Organic Framework MIL-89 nanoparticles garnered remarkable attention for their widespread use in technological applications. However, the impact of these nanomaterials on human and environmental health is still limited, and concerns regarding the potential risk of exposure during manipulation is constantly rising. Therefore, the extensive use of nanomaterials in the medical field necessitates a comprehensive assessment of their safety and interaction with different tissues of the body system. In this study, we evaluated the systemic toxicity of nanoMIL-89 using Zebrafish embryos as a model system to determine the acute developmental effect. Zebrafish embryos were exposed to a range of nanoMIL-89 concentrations (1 – 300 µM) at 4 h post-fertilization (hpf) for up to 120 hpf. The viability and hatching rate were evaluated at 24–72 hpf, whereas the cardiac function was assessed at 72 and 96 hpf, and the neurodevelopment and hepatic steatosis at 120 hpf. Our study shows that nanoMIL-89 exerted no developmental toxicity on zebrafish embryos at low concentrations (1–10 µM). However, the hatching time and heart development were affected at high concentrations of nanoMIL-89 (> 30 µM). Our findings add novel information into the available data about the in vivo toxicity of nanoMIL-89 and demonstrate its innocuity and safe use in biological, environmental, and medical applications. Other Information Published in: Toxicology Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.toxrep.2022.04.016